2021
DOI: 10.1007/s12144-021-01582-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial status during the prevalence of COVID-19 disease: the comparison between healthcare workers and general population

Abstract: The prevalence of COVID-19 disease continues to be a significant psychosocial status among health care workers (HCWs) and the general population worldwide. This cross sectional study aimed to compare the psychosocial status between healthcare workers and general population during the prevalence of COVID-19 disease in southeast Iran. Totally 415 health care workers of a medical service center for COVID-19 patients and 1023 people of general population participated in the study. An online socio-demographic chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 45 publications
0
29
1
Order By: Relevance
“…Due to its direct relationship with human health, the healthcare sector is now one of the most important areas of sustainable development in human societies ( Zakeri et al, 2021b ). Nurses provide the majority of the healthcare services in an epidemic ( Wan et al, 2020 ), and they have the most contact with patients ( Zakeri et al, 2021d ). During the COVID-19 epidemic, front-line nurses face numerous health challenges ( Wan et al, 2020 ) and are directly at risk when treating and caring for COVID-19 patients; as a result, severe stress and problems they experience at work lead to physical, mental, and social disorders ( Kisa, 2020 ; Wan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its direct relationship with human health, the healthcare sector is now one of the most important areas of sustainable development in human societies ( Zakeri et al, 2021b ). Nurses provide the majority of the healthcare services in an epidemic ( Wan et al, 2020 ), and they have the most contact with patients ( Zakeri et al, 2021d ). During the COVID-19 epidemic, front-line nurses face numerous health challenges ( Wan et al, 2020 ) and are directly at risk when treating and caring for COVID-19 patients; as a result, severe stress and problems they experience at work lead to physical, mental, and social disorders ( Kisa, 2020 ; Wan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nurses are the major healthcare workforce in an epidemic ( Wan et al, 2020 ) and have the most contact with patients ( Kisa, 2020 ). Frontline nurses face many health challenges during the COVID-19 epidemic ( Zakeri et al, 2021d ), are directly at risk when treating and caring for COVID-19 patients, and thus experience severe stress and problems in the workplace leading to physical, mental, and social disorders, as well as burnout ( Kisa, 2020 ), anxiety, stress, and depression ( Wan et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Certainly, the general public has experienced anxiety, stress, fear, uncertainty, and insecurity as a result of the COVID‐19 pandemic (Zakeri, Hosseini Rafsanjanipoor, Kahnooji, et al, 2021 ; Zakeri, Hosseini Rafsanjanipoor, Sedri, et al, 2021 ). Studies have shown that in times of crisis, particularly infectious crises, psychological responses such as anxiety, depression, stress, and fear can have a negative impact on people's health (Pappas et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the COVID‐19 pandemic have revealed that individuals' physical and mental health is critical to live a healthy life and cope with crises such as COVID‐19 (Hossini Rafsanjanipoor et al, 2021 ; Rossi et al, 2020 ; Zakeri, Hosseini Rafsanjanipoor, Sedri, et al, 2021 ). Examining factors related to individuals' general health can be used in planning and potential interventions to improve it in individuals affected by the COVID‐19 pandemic and similar crises.…”
Section: Introductionmentioning
confidence: 99%